Implementation of the Corporate Social Responsibility (CSR) Program PT. Indonesia Power Kamojang Coffee Cultivation Activities in Maintaining Corporate Image and Community Based Economic in Pandemic Time - Melly Maulin Purwaningwulan; Muhamad Fahad Alfarisi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to analyze the implementation of the Corporate Social Responsibility (CSR) Program of PT. Indonesia Power Kamojang through Kamojang Coffee Cultivation Activities in Maintaining Company Image and Community-Based Economy in the Pandemic Period. This research uses a qualitative approach with a descriptive study. Data collection techniques were carried out through in-depth interviews, non-participant observation and documentation. Determination of informants by purposive sampling technique and informants consist of 3 key informants, and 6 supporting informants. Problem Identification, PT. Indonesia Power Kamojang held a Focus Group Discussion through social mapping with the result that coffee was the main commodity in the Kamojang area. Planning, the company organizes, interprets programs, and implements CSR programs. Communication, the company takes a communication approach through internal media to the group by providing direction, assistance with facilities, and holding training for the group. Communication barriers that occur are divided into personal, semantic, and technical barriers. For Evaluation, the internal process is carried out once a quarter, while the external evaluation is carried out once a year. The conclusion of this research is the CSR program of community-based Kamojang Coffee Cultivation, PT. Indonesia Power Kamojang can maintain its corporate image by actively participating in implementing social responsibility. Suggestions for this research PT. Indonesia Power Kamojang can improve the performance of CSR programs and have more opportunities to develop the potential of the surrounding area.